2021
DOI: 10.32598/ahs.10.3.225
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Compassion-focused Therapy on Anxiety and Depression in the Mothers of Children With Cerebral Palsy

Abstract: Background & Aims of the Study: Cerebral Palsy (CP) is the most common chronic motor disability in children. CP can cause depression and anxiety in the mothers of affected children. The present study aimed to investigate the effects of Compassion-Focused Therapy (CFT) on anxiety and depression in the mothers of children with CP. Materials and Methods: This was an experimental study with a pre-test, post-test and follow-up and a control group design. The study sample consisted of 40 mothers of children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…These scores were considered as pretest. We included 50 people (25 couples) in each group by using of G-power software with an effect size of 1.8, a test power of 0.90, and α=0.05 [14]. The couples were randomly divided into emotionally focused couple therapy (n=25) and control groups (n=25) using a simple random coin-throwing method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These scores were considered as pretest. We included 50 people (25 couples) in each group by using of G-power software with an effect size of 1.8, a test power of 0.90, and α=0.05 [14]. The couples were randomly divided into emotionally focused couple therapy (n=25) and control groups (n=25) using a simple random coin-throwing method.…”
Section: Methodsmentioning
confidence: 99%
“…[15]. Khoshvaght et al [14] reported an alpha Cronbach coefficient of 0.81 for the Persian version of the questionnaire. In this study, Cronbach's alpha coefficient was 0.86 for the BDI.…”
Section: Methodsmentioning
confidence: 99%
“…Forty-five women with breast cancer were selected and randomly divided into two experimental groups and one control group (n=15 per group). In this study, the sample size was selected by the G-Power software (α= 0.05, test power= 0.90, and effect size= 1.71) 21 . The random coin-throwing method was used for allocating participants to experimental and control groups.…”
Section: Design and Participantsmentioning
confidence: 99%
“…The scores reflect a wide spectrum of symptoms' severity, and each set of questions is scored from 0 to 3 (from mild to severe). Khoshvaght et al [25] reported the Cronbach α coefficient of 0.81 for the questionnaire. In this study, the Cronbach α was obtained at 0.83.…”
Section: Research Instruments Beck Depression Inventory-iimentioning
confidence: 99%